Application of a Big Data Platform in the Course of Java Language Programming - Lin, Dingbao (International journal of emerging technologies in learning, 2016)
This study designs a big data teaching platform that adopts the big data technology of Hadoop as its core. The platform provides a method of searching teaching video data and integrates the technologies of data encryption and intelligent recognition. The teaching functions of this advanced platform include teaching audio–visual presentation, intelligent data recognition, data-mining sharing, and data storage sharing. The method of comparative teaching is adopted to test the actual effect of the teaching platform on teaching Java language programming to students majoring in computer. Results show that the platform exhibits good teaching applicability, significantly improves the examination achievements, learning interest, independent learning ability, and innovation ability of students, and therefore indicates a promising application prospect and research value.